Kajian Politik Hukum Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024 Tentang Pemisahan Pemilihan Umum Nasional dan Lokal - Suryana, Eka Pala; Kartika, Adhitya Widya; Fikri, Abdullah (Universitas Muhammadiyah Kotabumi, 2025)
The Constitutional Court Decision Number 135/PUU-XXII/2024 ruled the separation of national and local elections, with the Court’s considerations emphasizing that previous electoral practices had led to excessive workloads for election organizers, political party pragmatism, the marginalization of regional development issues, institutional fatigue and casualties, as well as voter fatigue and a decline in the quality of popular sovereignty. This study examines the legal politics underlying the Constitutional Court’s decision and its juridical implications by employing both a case approach, which analyzes legal disputes in the electoral law domain, and a conceptual approach, which explores the transformation of electoral concepts. The findings demonstrate that the legal politics of Decision Number 135/PUU-XXII/2024 aim to enhance the quality of democracy, since democratic elections play a vital role in safeguarding state integrity, establishing representative institutions, and ensuring effective governance, all of which must be conducted in accordance with the general principles of democracy. Furthermore, the juridical impact of the decision highlights the urgency of strategic measures in electoral governance, particularly the need for immediate legislative revisions of the Electoral Law to guarantee voter accessibility, consolidate political parties, and rationalize the workload of election organizers, thereby providing a clear operational legal basis for the transitional period.